Analysis of the Practice of Istishna Contracts in Online Buying and Selling Based on Islamic Law - Hana Fauziah Balqis; Irvan Iswandi; Moch. Syafii (JOURNAL of LEGAL RESEARCH, 2022)
This study analyzes the practice of istishna' contract in online buying and selling based on Islamic law. The purpose of this study is to find out and understand the practice of Istishna' contract in buying and selling online at the Headway Leather store and analysis of the practice of Istishna' contract in buying and selling online at the Headway Leather store based on Islamic law. The research method uses a qualitative approach with in-depth interviews with sellers and buyers at the Headway Leather store, totaling 5 informants. The results of the study stated that the Headway Leather online store markets the goods it sells online using Instagram social media, consumers order goods to sellers via DM Instagram and Whatsapp, sellers and buyers make transactions and submit specifications of goods from buyers to sellers. Then the seller asks the manufacturer to make the goods, and the manufacturer makes the goods according to specifications. When the goods are finished, the goods are delivered to the buyer. The practice of istishna' contract in online buying and selling applied at the Headway Leather online store is in accordance with the provisions of the istishna' contract according to the perspective of Islamic law.